2012
DOI: 10.1016/j.polymertesting.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Volume changes in a filled elastomer studied via digital image correlation

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractVolumetric strains in a filled SBR specimen subjected to cyclic uniaxial tension with increasing extensions are studied. Digital image correlation is used to follow the kinematics of two orthogonal free faces. A volume expansion is observed past a critical elongation, which can be interpreted as the onset of cavitation. Under unloading, the volume retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
6
19
0
1
Order By: Relevance
“…This result has been corroborated by other studies cited in [4]. Assuming that the material softening is due to damage within the rubber matrix, the average molecular weight of the network chains, characterized by swelling tests, should increase significantly.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result has been corroborated by other studies cited in [4]. Assuming that the material softening is due to damage within the rubber matrix, the average molecular weight of the network chains, characterized by swelling tests, should increase significantly.…”
Section: Introductionsupporting
confidence: 83%
“…Recent experiments measuring the macroscopic volume change during cyclic uniaxial tension [4] have shown that while vacuoles form upon the first stretch, they do not reopen during the subsequent loadings and therefore the mechanical softening cannot be explained by the presence of voids. This result has been corroborated by other studies cited in [4].…”
Section: Introductionmentioning
confidence: 99%
“…A very similar behavior was observed in a natural rubber matrix filled with the same type of CB. 35 These results have also been quantitatively confirmed by macroscopic volume variation tests [33][34][35][36] and provide a mechanistic proof of earlier reports of volume change of filled elastomers in uniaxial tension. 37,38 Such nanocavities and the associated change in volume in uniaxial extension is unusual for rubbers and was only observed for large values of extension k. In the case of the crack tip, the high stress strongly promotes the nucleation of nanovoids in the tip region, which may further lead to the ligaments structure revealed during crack propagation.…”
supporting
confidence: 82%
“…From the displacement of droplet barycenters, one can compute the axial strain ε yy = ( Y/L 0 ), the transversal one ε xx = ( X/l 0 ) and the Poisson's ratio = − (ε xx /ε yy ). Notice that although the Poisson's ratio is generally assumed to be constant, near to 0.5 (incompressibility), some research has shown that volume changes occur within elastometric materials during deformation processes and are attributed to damage mechanisms [40,41,35,42] -so the Poisson's ratio decreases with deformation, depending on the damage. Thus, for the sake of clarity we define the initial and the ruptured Poisson's ratios, meaning the undamaged and damage ratio.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Much work has been done into the investigation of the mechanical properties of PDMS and their potential tunability [26,28,21,29,30,16,31,32,17,33,4,[34][35][36][37]. The largest observed tensile stiffness, using 10:1 PDMS, to date is less than 4 MPa [30] after 7 days post-baking at 100 • C and less than 3 MPa for post-baking at 200 • C during 18 min [37].…”
Section: Introductionmentioning
confidence: 99%